ANALISIS HUKUM MENGENAI KEWAJIBAN ENDORSER TERHADAP PENGANJURAN PRODUK PADA MEDIA SOSIAL - Ladynanti, Prizqa; Permana, Sudaryat (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Promotion of a product/service in the right way needs to be done in order to attract the attention of consumers. One of the most effective ways of promotion in this era is through endorsements. Endorsement is an activity in which business actors collaborate with public figures to promote their products on social media. However, endorsement activities must of course be accompanied by responsibilities by the endorser in order to create consumer protection. The position of endorsers in Indonesia based on the ITE Law is equivalent to that of senders/manufacturers, then based on the Consumer Protection Law it is equivalent to business actors. Furthermore, the responsibility of the endorser in Indonesia under the ITE Law is the same as that of the sender/producer, then the responsibility of the endorser under the Consumer Protection Act is the same as that of business actors. Endorsers are responsible for all information they distribute to promote a product/service through their social media.